The sustainable society index: its reliability and validity - Witulski, N.; Dias, J. G. (Ecological Indicators, 2020)
The Sustainable Society Index (SSI) is known as a comprehensive index that contains substantive aspects of all three dimensions of sustainable development (SD): social, environmental, and economic. This paper assesses the reliability (internal consistency) and external validity of the SSI for 154 developing and developed countries for the year 2016. Confirmatory factor analysis and standard measures of reliability are used to assess the internal consistency, and we use Kendall rank correlation coefficients to compare the country rankings of the social and economic dimension with the Human Development Index (HDI), and of the environmental dimension with the Environmental Performance Index (EPI). Our results clearly demonstrate that there are indicators within each dimension that need to be removed to achieve construct reliability. The three modified indices of the SSI show strong internal consistency. The external validity of the modified indices is supported as the country rankings are similar to those of the HDI and EPI and show a high correlation in 2014 and 2016. In the current sustainable development debate, this study highlights the need for a detailed statistical analysis and adjustment of the indices that represent sustainable development to achieve a theoretical and statistically reliable representation of the concept.